Absence of Curli in Soil-Persistent Escherichia coli Is Mediated by a C-di-GMP Signaling Defect and Suggests Evidence of Biofilm-Independent Niche Specialization - Somorin, Yinka M.; Vollmerhausen, Tara; Waters, Nicholas; Pritchard, Leighton; Abram, Florence; Brennan, Fiona; O’Byrne, Conor (Frontiers in Microbiology, 2018)
Escherichia coli is commonly viewed as a gastrointestinal commensal or pathogen although an increasing body of evidence suggests that it can persist in non-host environments as well. Curli are a major component of biofilm in many enteric bacteria including E. coli and are important for adherence to different biotic and abiotic surfaces. In this study we investigated curli production in a unique collection of soil-persistent E. coli isolates and examined the role of curli formation in environmental persistence. Although most soil-persistent E. coli were curli-positive, 10% of isolates were curli-negative (17 out of 170). Curli-producing soil-persistent E. coli (COB583 and COB585) displayed significantly more attachment to quartz sand than the curli-negative strains. Long-term soil survival experiments indicated that curli production was not required for long-term survival in live soil (over 120 d), as a curli-negative mutant BW25113 ΔcsgB had similar survival compared to wild type BW25113. Mutations in two genes associated with c-di-GMP metabolism, dgcE and pdeR, were identified in eight curli-deficient soil-persistent strains, although this genotype did not significantly impair their survival in soil compared to curli-positive strains. These mutations were shown to be responsible for the curli-deficient phenotype. Overall, the data indicate that curli are dispensable for the long-term persistence of E. coli in soil environments and point to the possibility that niches may exist in the soil that can support long-term survival independently of biofilm formation.